The preliminary design of desktop desk : an ergonomics approach - Sajimar, Abdul Gajir (2009)
This study is about designing a desktop desk using ergonomics technique in order to avoid or minimize the chance of developing Musculoskeletal Disorders (MSD) among the workers. MSD happens due to the product or tools that is not ergonomics. MSD starts to develop when a workers is doing a job repeatedly. The problem statement for this study is the musculoskeletal disorder that occurs when the action was doing statically for a long period time and repetitive. There are three objectives for this study. The first objective of this study is to design a desktop desk with ergonomics approach using Solidworks. The preliminary design will be design using Solidworks. The second objective is to simulate the designed desktop table using Algor. This is to analyze the force affecting the desktop when it is subjected to the force and its deformation value. This study also uses the algor to simulate the critical part like the vertical structure that supports the desktop desk. The third objective is to analyze the bending moment of the desk. First stage of this study was collecting data via literature review and find out the problem that occur in the desk that have been designed. This design will be upgraded and modified to overcome and ensure that the same problem not occur again in the future. In the end, this study is targeting to overcome the musculoskeletal disorder problem that has been a nightmare to the human being.